PENGGUNAAN E-LKPD BERBASIS VIRTUAL LABORATORY PADA MATERI GELOMBANG BERJALAN DAN GELOMBANG STASIONER UNTUK MENINGKATKAN HASIL BELAJAR KOGNITIF SISWA KELAS XI SMAN 1 KEPENUHAN - Azrul Hamidi; Mitri Irianti; Syahril Syahril (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: To improve the quality of learning and improve student’s cognitiveabilities in experimental activities, teachers can use various supporting media, forexample by using an E-LKPD based on virtual laboratory. The use of E-LKPD based onvirtual laboratory in physics learning is very important, considering the lowopportunity for students to be able to carry out practical activities due to limitedpracticum facilities and infrastructure. E-LKPD based on virtual laboratory in thisstudy was developed on the material of Traveling Waves and Standing Waves for HighSchool Students. The purpose of this study was to determine the effect of using E-LKPDbased on virtual laboratory in learning activities to improve student’s cognitivelearning outcomes. This type of research is quantitative using experimental researchmethods and Quasi Eksperimental Design in the form of Nonequivalent Control GroupDesign. The population used in this study were all students of class XI MIPA SMAN 1Kepenuhan with 84 students spread over three classes. The sample in this study usedtwo classes, class XI MIPA 2 with 27 students called as Experiment class and class XIMIPA 3 with 28 students called as Control class which were selected based on theresults of the normality test and homogeneity test. From the results of the study, it canbe concluded that there is an effect of using E-LKPD based on virtual laboratory oncognitive learning outcomes students of SMAN 1 Kepenuhan, so that the use of E-LKPDbased on virtual laboratory can improve cognitive learning outcomes of XI high schoolstudents. Thus, the E-LKPD based on virtual laboratory is effectively used as teachingmaterial for Walking Waves and Stationary Waves in Physics learning.Keywords: E-LKPD Based on Virtual Laboratory, Cognitive Skill Outcomes, TravelingWaves and Stationary Waves